Role of weak C—H…O and strong N—H…O intermolecular interactions on the high-symmetry molecular packing of trans-cyclohexane-1,4-dicarboxamide - García Reyes, Fernando (2018)
An unpredicted fourfold screw N—H.O hydrogen bond C(4) motif in a primary dicarboxamide (trans-cyclohexane-1,4-dicarboxamide, C8H14N2O2) was investigated by single-crystal X-ray diffraction and IR and Raman spectroscopies. Electron-density topology and intermolecular energy analyses determined from ab initio calculations were employed to examine the influence of weak C—H.O hydrogen-bond interactions on the peculiar arrangement of molecules in the tetragonal P43212 space group. In addition, the way in which the co-operative effects of those weak bonds might modify their relative influence on molecular packing was estimated from cluster calculations. Based on the results, a structural model is proposed which helps to rationalize the unusual fourfold screw molecular arrangement.